Calibration Technique for Recovery of Short Duration Aerodynamic Force. (4th March 2014) - Sahoo, Niranjan; Babu, P. Ramesh
Abstract : Force measurement is one of the key issues for design of high speed vehicle configurations. They are routinely tested in impulse facilities where the test duration is in the order of few milliseconds. Since, the experiments are performed in short test times, it is expected that the model never achieves the steady state. So, the measurement diagnostics must account this fact while inferring the forces from the measured parameters. One of the methods is the determination of characteristics system response function by including the dynamics of the system. The aim of this work is to develop a calibration experimental setup and measure axial force on generic aerodynamic body configurations during a short time ( 0.6 ms). A generic aerodynamic model attached to a "stress bar" is suspended freely and an impulse load is applied at the tip of the model. An accelerometer fitted with the model records the signal corresponding to the motion of the model. Then, the system characteristics function (impulse response function) is obtained from input force history and output accelerometer signal and further used to predict any unknown forces of similar nature. The recovered forces are compared well with the applied ones with a reasonable accuracy of± 5 %.